2016
DOI: 10.1080/15389588.2016.1186273
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of young Indigenous drink drivers in Queensland, Australia

Abstract: There were limited differences between females and males or recidivists and nonrecidivists at first conviction. Convictions for drink driving may provide an opportunity for early alcohol intervention with Indigenous young drivers (<20 years) because it is likely to be an individual's first alcohol-related conviction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…For example, Impinen et al (2009) [10] found that recidivists are, on average, younger and have higher blood alcohol concentration (BAC) than non-recidivists at the time of their first offense. Fitts, Palk, Lennon, and Clough (2017) [11] reported that subjects with a very high number of BAC convictions are more likely to re-offend, confirming the results of Chou et al (2005) [12] and Morrison, Begg, and Langley (2002) [13]. Others have attempted to predict recidivism using a combination of demographic variables and personality characteristics, employing statistical procedures such as multiple regression, discriminant function analysis, and logistic regression (for a review, see Nochajski & Stasiewicz, 2006 [14]).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Impinen et al (2009) [10] found that recidivists are, on average, younger and have higher blood alcohol concentration (BAC) than non-recidivists at the time of their first offense. Fitts, Palk, Lennon, and Clough (2017) [11] reported that subjects with a very high number of BAC convictions are more likely to re-offend, confirming the results of Chou et al (2005) [12] and Morrison, Begg, and Langley (2002) [13]. Others have attempted to predict recidivism using a combination of demographic variables and personality characteristics, employing statistical procedures such as multiple regression, discriminant function analysis, and logistic regression (for a review, see Nochajski & Stasiewicz, 2006 [14]).…”
Section: Introductionmentioning
confidence: 99%
“…Indigenous people are more likely to drink and drive if they are in non‐urban areas [21], are aged less than 25 years [21] and have multiple drink driving convictions [22,23]. Specifically, Indigenous drink drivers from remote areas [24] are more likely to re‐offend and to record a higher range blood alcohol concentration (≥0.15 g/100 ml in Australia) [25].…”
Section: What Do We Know About Indigenous Australians Who Drink and D...mentioning
confidence: 99%
“…For example, some studies and government reports present overall Indigenous drink driving rates only by jurisdiction [3] or by recidivism rates and associated demographic and offence characteristics [22,23,25]. One study compared Indigenous and non‐Indigenous drink drivers [31], while another study compared Indigenous first‐time convicted and Indigenous repeat drink drivers [25]. This makes it difficult to determine regions of high risk and impact of policy and programs on drink driving.…”
Section: What Do We Know About Indigenous Australians Who Drink and D...mentioning
confidence: 99%
See 1 more Smart Citation